Analysis of Influence of Abrasive Material Variation and Spray Pressure Variation in Coating Epoxy of Astm A36 Steel Toward Impact Resistance and Corrosion Rate - Herman Pratikno; Bima Satriya Willy Harsa; Sholihin Sholihin (International Journal of Offshore and Coastal Engineering (IJOCE), 2020)
Corrosion is a decrease in material quality caused by environmental influences. One of the methods commonly used to control corrosion is coating. In the coating process, the use of spray is the better method compared to roll and brush. Before coating is applied, the choice of abrasive material during the sand blasting process can determine the success of the coating. This research was conducted to analyze the effect of variations in abrasive material and spray pressure on the coating process of ASTM A36 steel material on its impact resistance, corrosion rate, and adhesion forces. Variation of abrasive material used were steel grit and silica. The spray pressure variations used were 2.5, 3.5, and 4.5 bar. The result of corrosion rate testing on variation with steel grit abrasive material and spray pressure of 4.5 bar has the lowest corrosion rate, with the value of 0.00124 mm/a. The highest adhesion strength test result of 9.07 MPa was obtained from variations with steel grit abrasive material and spray pressure of 4.5 bar. Impact test result using a variation with steel grit abrasive materials and a spray pressure of 4.5 bar yield the highest value, with the value of 2.287 joules.